PESANTREN SAINS: EPISTEMOLOGY OF ISLAMIC SCIENCE IN TEACHING SYSTEM - Mohamad Yasin Yusuf (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
Muslims around the world mostly was under the domination of the West in the mastery of science and technology. Establishing educational institutions that are based on science and technology is one of the ways to solve the problem.This study had the purpose to examine the epistemology of science in the teaching system in SMA Trensains boarding school Tebuireng Jombang. Applying the method of field research through qualitative approach and philosophical analyses, this study revealed that SMA Trensains Tebuireng Jombang applied "Islamic Science" in which science is constructed based on the revelation of God. It is meant that in Islamic epistemology, revelation and the Sunnah are the sources which are inspiring for building sciences. It is hoped that the building the Islamic epistemology of science will bear pious Muslim generation in religious field and proficient in science and technology, and it will impact to the glory of Islamic civilization in the future.